BIOMEDICAL ENGINEERING IN GHANA - Richard Quansah Amissah; Albert Kwesi Atchurey; Loretta Appiah; Elvis Kofi Fiakumah; Emmanuel Gyapong-Korsah; John Boadu; Emmanuel Tetteh; Emmanuel Offei; Elsie Effah Kaufmann (European Scientific Journal, ESJ, 2013)
Even though Biomedical engineering contributes significantly to health care delivery, its full potential is yet to be comprehended and appropriated by the health sector in Ghana. This paper therefore provides a comprehensive description of Biomedical engineering in Ghana as of November, 2011 and makes recommendations based on the situation in Ghana and some developed countries.Biomedical engineering in Ghana started in the late 1990s thanks to the combined efforts of the pioneering stakeholders in the field. Since then, the country has seen a steady increase in the number of institutions engaged in educating and employing biomedical engineers. Though Bioinstrumentation is the dominant subspecialty in Ghana, it employs less than half the graduates of the field annually. Regulatory bodies for medical devices and consumables exist in the country, though not operating at full capacity.For Biomedical engineering to be firmly established in Ghana there should be a massive campaign to educate the public on its relevance. Educational institutions should strive to supply well trained biomedical engineers to meet increasing demands, while the government provides funds for the necessary logistics for such a cause. To avoid redundancy in the roles each identified regulatory body should have clearly defined and differentiated tasks.